1996
DOI: 10.1088/0953-4075/29/6/003
|View full text |Cite
|
Sign up to set email alerts
|

Resonant photoionization of atomic lithium in the region of the first and second inner-shell thresholds

Abstract: Using a dilute atomic beam of lithium crossed with monochromatized vacuum-ultraviolet synchrotron radiation from the undulator beamline BW3 at HASYLAB, the resulting singly ionized lithium signal was measured in the photon energy region corresponding to the threshold for inner-shell excitation. The photoion spectra were measured with a photon energy resolution of approximately 10000, facilitating the identification of a number of window-type resonances above the threshold. New R-matrix calculations are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
33
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 24 publications
8
33
1
Order By: Relevance
“…Here many lower Rydberg states associated with the 1s2s 1 S threshold appear. Kiernan et al [9] identified the resonance at 65.874(10) eV as the ͑1s2s͒ 1 S, 6p; our results support this identification. However, we also found that the structure at 65.860 eV is a ͑1s2p͒ 3 P, 4d resonance.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…Here many lower Rydberg states associated with the 1s2s 1 S threshold appear. Kiernan et al [9] identified the resonance at 65.874(10) eV as the ͑1s2s͒ 1 S, 6p; our results support this identification. However, we also found that the structure at 65.860 eV is a ͑1s2p͒ 3 P, 4d resonance.…”
supporting
confidence: 86%
“…1, we present the theoretical prediction of the photoionization cross section of lithium in the entire region of interest. The experimental result of Kiernan et al [9] is also given for comparison. The energy uncertainty in the experiment is 610 meV .…”
mentioning
confidence: 92%
See 3 more Smart Citations